TRADISI PEGI TEPAT MASYARAKAT DESA TALANG PETAI KABUPATEN MUKOMUKO DALAM PERSPEKTIF HUKUM ISLAM - Jamal Mirdad; Al Ikhlas (Institut Agama Islam Negeri Batusangkar, 2018)
Pilgrimage tradition in Indonesia is a phenomenon that has not been eradicated by the times. The more modern and sophisticated technology, the more pilgrims come. In each city and region there are many people who cult certain graves to the point that the tomb can solve their problems. The tradition of the grave pilgrimage or the term in Mukomuko Regency is